Emerging technologies: Virtual reality, augmented reality, and robotics - Cózar-Gutiérrez, Ramón; López-García, Alejandro (Peter Lang, 2023)
Emerging technologies are made up of state-of-the-art software and hardware whose developments converge in innovative procedures and practices capable of proposing methodological alternatives and contributing to educational efficiency. In recent years, abundant research and numerous national and international reports have tackled the most relevant technological trends and practices in educational contexts. This chapter explores virtual reality (VR), augmented reality (AR), and educational robotics (ER) as the main emerging technologies. The text defines and characterizes their scope, highlighting their possibilities and limitations for practical implementation. Remarkable benefits are observed in terms of improvements in interest, motivation, and academic results, among others. The importance of increasing training to bridge the gaps in teachers’ knowledge, instrumental skills, and pedagogical practices is also emphasized. The chapter concludes by underscoring that educational administrations must make a firm commitment to these technologies, as a turning point to transform the quality of learning in the 21st century.
Keywords: Historia - Estudio y enseñanza; Tecnología educativa; Educational technology; Virtual environments; Immersive technologies; Emerging software; Educational technology